2013
DOI: 10.1186/1471-2474-14-6
|View full text |Cite|
|
Sign up to set email alerts
|

Time course of 25(OH)D3 vitamin D3 as well as PTH (parathyroid hormone) during fracture healing of patients with normal and low bone mineral density (BMD)

Abstract: BackgroundUntil now the exact biochemical processes during healing of metaphyseal fractures of healthy and osteoporotic bone remain unclear. Especially the physiological time courses of 25(OH)D3 (Vitamin D) as well as PTH (Parathyroid Hormone) the most important modulators of calcium and bone homeostasis are not yet examined sufficiently. The purpose of this study was to focus on the time course of these parameters during fracture healing.MethodsIn the presented study, we analyse the time course of 25(OH)D3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Vitamin D status is indicative of calcium absorption and bone mineralization [ 80 ], and a considerable expanse of knowledge describes the relationship between vitamin D deficiency and bone health [ 80 87 ]. Genetic, environmental, and cultural factors associated with 25[OH]D deficiency [ 88 ] increase the risk of osteoporosis [ 89 ] and are a major contributor to fracture risk [ 90 ].…”
Section: Functional Roles Of Vitamin D Relevant To the Athletementioning
confidence: 99%
“…Vitamin D status is indicative of calcium absorption and bone mineralization [ 80 ], and a considerable expanse of knowledge describes the relationship between vitamin D deficiency and bone health [ 80 87 ]. Genetic, environmental, and cultural factors associated with 25[OH]D deficiency [ 88 ] increase the risk of osteoporosis [ 89 ] and are a major contributor to fracture risk [ 90 ].…”
Section: Functional Roles Of Vitamin D Relevant To the Athletementioning
confidence: 99%
“…Clearly, given the multitude of physiological actions that require or involve vitamin D, including calcium and phosphate metabolism, osteoblast and osteoclast functions [58,115] bone collagen synthesis, and resorption [22] , the role of vitamin D in influencing bone metabolism in health and injury situations is surely a topic of considerable import and one that merits more comprehensive study, before discarding it out of hand. In particular, controlled prospective studies of well-defined samples that consider the state of prevailing calcium metabolism, as well as vitamin D serum and intraosseus levels over carefully considered time frames along with careful monitoring of the fracture healing process [76] may be helpful in efforts to examine any specific role vitamin D may have in optimizing fracture repair, as well as in preventing adverse fracture outcomes. In addition, use of carefully construed fracture and bone repair models that emulate human physiological processes quite closely, plus efforts to examine the role of vitamin D at all stages of the fracture healing process using advanced technologies [86] , plus attempts to discriminate the impact of vitamin D2 measures and supplements from D3 measures and supplements, which are three times more effective [102] may help to advance this present body of contention and ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…This latter argument seems reasonable, in light of similar conclusions by Fischer et al [1] , Fentaw et al [6] , and Gomberg et al [75] . However, given that Wolfl et al [76] who examined the time course of vitamin D levels during fracture healing in persons with fractures of healthy bone versus osteoporotic bone over an eight-week period found no intergroup differences, caution is advised in arriving at any conclusion as to whether vitamin D status at the time of fracture can affect fracture healing, or whether vitamin D supplementation is desirable. Although Degli Espositi et al [77] found osteoporosis drug treatment, especially when consistently applied in combination with calcium/vitamin D correlated with a lower risk of both re-fracture and all-cause mortality they do not definitively support a role for vitamin D supplementation in the fracture healing processes [1,67] .…”
Section: Overview Of Clinical Studiesmentioning
confidence: 99%
“…We found partly significantly different time courses of up-regulation of specific alkaline phosphatase (BAP) and transforming growth factor β1 (TGF-β1), as well as the bone resorption markers crosslinked C-telopeptide of type-I-collagen (β-CTX) and serum band 5 tartrate-resistant acid phosphate (TRAP5b). In addition, the time courses of vitamin D3 and parathyroid hormone (iPTH) have been examined because both parameters are important modulators of calcium and bone homeostasis, but no significant differences could be seen between the groups of normal and low BMD [ 12 ], [ 13 ]. Vitamin D3 and iPTH are affected of other metabolic pathways, thus it is not surprising that an influence of ESWT could not be shown here.…”
Section: Discussionmentioning
confidence: 99%
“…The time course of bone turnover markers, such as bone alkaline phosphatase (BAP), transforming growth factor β1 (TGF-β1), c-telopeptide of type-I-collagen (β-CTX), serum band 5 tartrate-resistant acid phosphate (TRAP5b), during fracture healing is a diagnostic method, which allows insight into ongoing processes and gives the possibility to recognize early an impaired healing course. A change of time courses of these turnover markers during fracture healing of bones with low BMD has already been observed [ 12 ], [ 13 ], [ 14 ]. In the present study, we want to evaluate whether external stimulation with ESWT has an impact on the healing process in bone with normal and low BMD.…”
Section: Introductionmentioning
confidence: 99%